ITS gene based molecular genotyping of Nepeta sheilae Hedge & R.A. King (Lamiaceae) endemic to Saudi Arabia - Alzeibr, Fahad MA; Ali, M Ajmal; Rahman, M Oliur; Hemaid, Fahad Al; Lee, Joongku; Kambhar, Sidanand V (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not available Bangladesh J. Plant Taxon. 27(1): 185-189, 2020 (June)